Hubungan Manajemen Waktu Perawat Pelaksana dengan Pendokumentasian Asuhan Keperawatan di Ruang Rawat Inap RSU GMIM Pancaran Kasih Manado - Suryani Hamid (PPNI UNIMMAN, 2025)
Documentation of nursing care is an obligation for nurses which is very important as proof of responsibility and nursing records in nursing actions, the better the performance of nursing including the documentation of nursing care. The purpose of this study is to determine the relationship between the time management of implementing nurses and the documentation of nursing care in the inpatient room of GMIM Pancaran Kasih Manado Hospital. The research was conducted using a descriptive analytical research method that is Cross sectional. The samples were taken based on the number of respoden 33 oarang using total sampling. Data collection was carried out by means of questionnaires. Furthermore, the data that has been collected is processed using the computer assistance of the SPSS program to analyze the chi-square statistical test with a safety level of α≤ 0.05.The results of the study showed that based on 33 research respondents, respondents with good time management and documentation of nursing care 13 (39.4%) and respondents with good management but poor documentation of nursing care 5 people (15.2%), then respondents with poor management 15 people (45.5%,) and respondents with poor time management and poor documentation 0 (0%), obtained the results of the Fisher's Exact test obtained a p value of >0.000 where the value of >α 0.005 shows that H0 is rejected and Ha is accepted. The conclusion in this study is that there is a relationship between nurse time management and nursing care documentation ρ=0.000 (α≤0.05) there is a gap between time management and nursing care documentation. This research suggestion is expected to be used as basic information data in further research.